2022
DOI: 10.2147/ijn.s387681
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Colloidal Stability of Commercial Amphotericin B Nanoformulations Using Dynamic and Static Multiple Light Scattering Techniques

Abstract: Background Amphotericin B (AmB) nanoformulations have been widely used for the treatment of invasive fungal infections in clinical practice, all of which are lyophilized solid dosage forms that improve storage stability. The colloidal stability of reconstituted lyophilized nanoparticles in an injection medium is a critical quality attribute that directly affects their safety and efficacy during clinical use. Methods In the present study, the colloidal stability of comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…All liposomal formulations have mainly similar sizes around 100 nm with a polydispersity index of around 0.2. These data are quite in agreement with those provided by Ye et al, whose findings showed an average diameter of 131 nm for a 1.0 mg/mL AmB diluted with a 5% dextrose solution [25], and more in line with the results exposed by Liu et al, which provided a value of 103 nm for the 4.0 mg/mL formulation [20]. As mentioned above, we monitored the properties of the liposomal formulations by DLS at specific time points to investigate changes occurring on the temporal scale.…”
Section: In Vitro Colloidal Stability Of Nanoformulationssupporting
confidence: 93%
“…All liposomal formulations have mainly similar sizes around 100 nm with a polydispersity index of around 0.2. These data are quite in agreement with those provided by Ye et al, whose findings showed an average diameter of 131 nm for a 1.0 mg/mL AmB diluted with a 5% dextrose solution [25], and more in line with the results exposed by Liu et al, which provided a value of 103 nm for the 4.0 mg/mL formulation [20]. As mentioned above, we monitored the properties of the liposomal formulations by DLS at specific time points to investigate changes occurring on the temporal scale.…”
Section: In Vitro Colloidal Stability Of Nanoformulationssupporting
confidence: 93%
“…A previous study used magnetic nanoparticles as a drug delivery method to increase the fungicidal action of polyene against clinical isolates of Candida species [237]. AmB's in vitro cytotoxicity and in vivo nephrotoxicity may both be considerably reduced by the use of nano‐formulations, such as the AmB cholesteryl sulphate complex (AmB‐CSC) and the AmB liposome (AmB‐Lipo) [238]. Another study has shown that PEG‐cholane nanoformulation of AmB was 15% more active than AmB in buffer [239].…”
Section: Discussionmentioning
confidence: 99%
“…Particle size distribution Determining the emulsion particle size distribution using PSS Nicomp 380 ZLS operating by the dynamic light scattering method is a crucial step in understanding the physical characteristics of the gum. Dynamic light scattering (DLS) has been widely used to measure the particle size and size distribution of various substances, including polysaccharides and nanoparticles, providing accurate and reliable results [18]. Measurements were conducted at ambient temperature on a minimum of two recently fabricated specimens.…”
Section: Emulsion Stability Indexmentioning
confidence: 99%